2014
DOI: 10.1016/j.gloplacha.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in significant and maximum wave heights in the Norwegian Sea

Abstract: This paper analyses 10 years of in--situ measurements of significant wave height

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…These findings extend the results found by Woolf et al (), Tsimplis et al (), Dodet et al (), Charles et al () and Feng et al (, ) and confirm the impact of the NAO and EA modes on SWH, MWP and MWD for both wind‐sea and swell component in the various areas of the North Atlantic. Our results are also in good agreement with Shimura et al (), who reported the correlation patterns over the North Atlantic between winter SWH and the same four climate indices, although for a different period (1960–1990).…”
Section: Discussionsupporting
confidence: 91%
“…These findings extend the results found by Woolf et al (), Tsimplis et al (), Dodet et al (), Charles et al () and Feng et al (, ) and confirm the impact of the NAO and EA modes on SWH, MWP and MWD for both wind‐sea and swell component in the various areas of the North Atlantic. Our results are also in good agreement with Shimura et al (), who reported the correlation patterns over the North Atlantic between winter SWH and the same four climate indices, although for a different period (1960–1990).…”
Section: Discussionsupporting
confidence: 91%
“…Since past historical data records often provide just data sampled at 3 or 6 hour intervals, the estimation of high return time wave heights can be seriously biased, as compared with high density data -half an hour or less: an application which is of growing importance as wave climate changes are being investigated (Feng et al 2014b;Passaro et al 2015;Liang et al 2016). A method has been supplied to estimate such a bias, and to compute Significant Wave Heights as a function of the return period.…”
Section: Resultsmentioning
confidence: 99%
“…Similar downward trend in extreme SWH was also observed off the west coast of Canada (Menendez et al, 2008). Moreover, in the North Sea and Gulf of Alaska, the long-term trend in the extreme SWH was also significant (Feng et al, 2014a;2014b;Menedez et al, 2008;Yao et al,2017). However, maybe due to the sparseness and less threat to coastal communities, the downward trends of the extreme SWH were not been paid much attention around the globe.…”
Section: Long-term Variability In Return Level Of Extreme Swhmentioning
confidence: 99%